Impact of COVID-19 on returns-volatility spillovers in national and regional carbon markets in China. (November 2022) - Mai, Te-Ke; Foley, Aoife M.; McAleer, Michael; Chang, Chia-Lin
Abstract: China wants to play a leading role in international carbon reduction and has ambitious reduction plans. China is one of the largest carbon emitters globally with an increasing trade volume in both national and regional markets. Owing to carbon emissions are regarded as key policy instruments and important financial assets thus It is important to analyze volatility spillovers between national and regional markets. The Diagonal BEKK model is used to examine daily financial returns, conditional covariances, and volatility spillovers across markets before, during, and after COVID-19. The empirical results show that the magnitudes of the spillovers during COVID-19 are much larger than before and after COVID-19 which implies the impact of COVID-19 on China's economy leads to greater risk transmission across carbon markets. China's experience (from regional to national) was useful in informing the channels of risk transmission and helping understand the relevance of carbon markets for investment decisions and public policymaking in the international carbon markets. Finally, we discuss the motivations, challenges, and possible forms of cooperation between China and the Eurozone on establishing a common carbon market are discussed. Highlights: carbon emissions are regarded as key policy instruments and important financial assets. This study analyze volatility spillovers between national and regional markets. The Diagonal BEKK model is used to examine volatility spillovers across markets before, during, and after COVID-19. Impact of COVID-19 on China's economy leads to greater risk transmission across carbon markets. China's experience (from regional to national) was useful in informing the channels of risk transmission.